2021
DOI: 10.1002/ange.202108870
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Nonoxidative Coupling of Methane Using Stable Solid Solutions

Abstract: Achieving efficient and direct conversion of methane under mild conditions is of great significance for innovations in the chemical industry. However, the efficiency and lifetime of most catalysts remain too far from practical requirements, since it is difficult to break the first C−H bond of methane as well as to suppress the following complete dehydrogenation (or overoxidation) and the resulting carbonaceous deposition (or CO2). Here, we report that wurtzite GaN:ZnO solid solutions exhibit unique and unprece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, Fig. 3d showed that the reaction order for methane over C@CZ was only 0.24, a value much smaller than other Ce-based catalysts (0.41-0.47) and other traditional NOCM semiconductors such as ZnO (0.46) and GaN (0.61), 22 suggesting that the surface of C@CZ can well adsorb methane, leading to very weak dependencies of the reaction rate on the gas-phase methane concentrations.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, Fig. 3d showed that the reaction order for methane over C@CZ was only 0.24, a value much smaller than other Ce-based catalysts (0.41-0.47) and other traditional NOCM semiconductors such as ZnO (0.46) and GaN (0.61), 22 suggesting that the surface of C@CZ can well adsorb methane, leading to very weak dependencies of the reaction rate on the gas-phase methane concentrations.…”
Section: Resultsmentioning
confidence: 83%
“…9 To date, only a few unsupported semiconductor photocatalysts can durably produce both ethane and H 2 under photocatalytic NOCM conditions. [21][22][23] In many cases, the H moieties detached from methane will combine with the lattice oxygen of catalysts and be released as water instead of H 2 . [15][16][17] Therefore, the oxidative regeneration of the catalyst at intervals is indispensable in these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…reported a GaN:ZnO solid solution for photocatalytic NOCM, which exhibits a productivity of 162 and 166 μmol·g −1 ·h −1 for ethane and hydrogen, respectively. [ 52 ] In addition to high catalytic activity superior to ZnO and GaN, GaN:ZnO solid solution achieves unique long‐term stability and superior coke‐resistance.…”
Section: Photocatalytic Methane C—c Couplingmentioning
confidence: 99%